2017
DOI: 10.1002/bdm.1999
|View full text |Cite
|
Sign up to set email alerts
|

Causal Models Drive Preference between Drugs that Treat a Focal versus Multiple Symptoms

Abstract: This research examines the effects of causal beliefs on drug preference. In three studies, 374 undergraduate participants imagined that they suffered from a focal symptom and then indicated their preference between a drug claiming to treat only the focal symptom (single treatment) and a drug claiming to treat the focal symptom and a nonfocal symptom (dual treatment) they thought resulted from a common-cause or from a different cause. Participants who thought that the symptoms resulted from different causes sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The results of the present study join with other studies that focus on the effects of causal-reasoning principles on judgments and inferences concerning artifacts (products) (e.g., Saporta-Sorozon, Danziger, & Sloman, 2017;Saporta-Sorozon & Bar-Eli, 2017;Saporta-Sorozon, 2018). Thus, it encourages studying the artifacts' (products') effects using the causal-reasoning framework.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…The results of the present study join with other studies that focus on the effects of causal-reasoning principles on judgments and inferences concerning artifacts (products) (e.g., Saporta-Sorozon, Danziger, & Sloman, 2017;Saporta-Sorozon & Bar-Eli, 2017;Saporta-Sorozon, 2018). Thus, it encourages studying the artifacts' (products') effects using the causal-reasoning framework.…”
Section: Theoretical Implicationssupporting
confidence: 87%
“…We focus on gambles for two reasons: First, consumers face many risky choices that share similar attributes with gambles. For example, when consumers choose between investments or grocers, they need to trade off investment returns (or discount magnitude) with investment risks (or discount frequency), or when they choose between medical treatments, they need to trade off the positive (partial or full treatment) and negative outcomes (side effects) of each treatment with the likelihood of these events (Saporta‐Sorozon, Danziger, & Sloman, ). Second, much of the literature examining differences between description‐based and experience‐based choice examined choice between gambles (Barron & Erev, ; Hertwig, ; Hertwig et al, ; Wulff, Mergenthaler Canseco, & Hertwig, in press).…”
mentioning
confidence: 99%
“…We focused on numerical data because the majority of the studies that examined the question of how data and preexisting causal knowledge are reconciled used numerical data (see, e.g., Fugelsang & Thompson, ; Perales et al, ; Waldmann & Hagmayer, ; for a summary, see also Rottman & Hastie, ). Yet, the few studies that used nonnumerical covariation data when examining the same question show the same pattern (see, e.g., Bes et al, ; Saporta‐Sorozon et al, ). Thus, we have a basis to assume that the pattern of our results will be similar for other ways of data representation.…”
Section: Discussionmentioning
confidence: 91%
“…Perales, Catena, and Maldonado (), for example, show that people expect a higher covariation between two cues when they believe they are effects of the same cause (e.g., a disease that causes secretion of two substances into the blood) than when they believe they are two causes for the same effect (e.g., two substances in the blood that cause a disease). Similarly, Saporta‐Sorozon, Danziger, and Sloman () recently found that the causal model held by people concerning the cause of two symptoms—same cause (e.g., nausea and vomiting) or different causes (e.g., insomnia and nausea) and not the covariation between the symptoms—affects participants' preference for a drug that treats the two symptoms rather than one. Lagnado and Sloman () demonstrate that people use temporal‐order and intervention cues to infer causal structure when the cues dominate the statistical information available.…”
Section: Conceptual Frameworkmentioning
confidence: 94%